2013
DOI: 10.1371/journal.pone.0073157
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the Validity of Asthma Associations for Eight Candidate Genes and Age at Diagnosis Effects

Abstract: BackgroundBefore the advent of genome-wide association studies (GWAS), ADAM33, ADRB2, CD14, MS4A2 (alias FCER1B), IL13, IL4, IL4R, and TNF constituted the most replicated non-HLA candidate genes with asthma and related traits. However, except for the IL13-IL4 region, none of these genes have been found in close proximity of genome-wide significant hits among GWAS for asthma or related traits. Here we aimed to assess the reproducibility of these asthma associations and to test if associations were more evident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Nevertheless, neither an individual GWAS study nor meta-analysis of GWAS has implicated ADRB2 the susceptibility gene for asthma. In our meta-analysis, we found that neither ADRB2 Arg/Gly16 nor ADRB2 Gln/Glu27 has significant association with asthma in Caucasian population, which further confirmed the results of previous published single GWAS and meta-analysis [51], [59], [60]. However, significant associations were found between ADRB2 Arg/Gly16 and asthma in Asian population, and this result contrasts with the results of studies recently conducted in Japan and Singapore [61][63], in which no single nucleotide polymorphisms in ADRB2 gene was found statistically significant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, neither an individual GWAS study nor meta-analysis of GWAS has implicated ADRB2 the susceptibility gene for asthma. In our meta-analysis, we found that neither ADRB2 Arg/Gly16 nor ADRB2 Gln/Glu27 has significant association with asthma in Caucasian population, which further confirmed the results of previous published single GWAS and meta-analysis [51], [59], [60]. However, significant associations were found between ADRB2 Arg/Gly16 and asthma in Asian population, and this result contrasts with the results of studies recently conducted in Japan and Singapore [61][63], in which no single nucleotide polymorphisms in ADRB2 gene was found statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…Genome-wide association study (GWAS) has been productive genotyping method to test a vast number of single nucleotide polymorphisms and assess their relations with complex diseases and phenotypes [57] . Since the first GWAS investigating susceptibility gene for asthma published in 2007 [58] , more than ten GWAS of asthma have been performed in Caucasian, Mexican, and African-ancestry populations [51] , [59] , [60] and more recently in Japan and Singapore of Asian populations [61] [63] . Nevertheless, neither an individual GWAS study nor meta-analysis of GWAS has implicated ADRB2 the susceptibility gene for asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation may be due in part to the differing LD patterns displayed by genetic variants between racial/ethnic groups (Shifman et al 2003; Xu et al 2007). It is also possible that a portion of the previous associations identified in adult studies of asthma susceptibility were age-dependent and may not have the same impact in a pediatric cohort (Castro-Giner et al 2010; Pino-Yanes et al 2013). We must also consider the possibility that the original findings reported in published GWAs studies were false positives or spurious associations.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other diseases, allergy and asthma appear to be arguably multifactorial and multigenic disorders, and therefore it has not been possible identify till now one or a set of specific genes that may be genetic markers [57,81], although recent paper identifies the involvement of GSTO2 loci in asthma, and GSTA1 as risk factor for asthma and allergies in Italian patients [56], while Genome-wide association studies (GWAS) represent the most powerful approach for asthma, have identified several distinct others genotypes from IL-18R1, IL-33, SMAD3, ORMDL3, HLA-DQ and IL-2RB loci [31].…”
Section: Discussionmentioning
confidence: 99%